Crystal structure of 4-[(2-methoxyphenyl)carbamoyl]butanoic acid, C12H15NO4 - Hanifa, B.; Muhammad, Sirajuddin; Khan, Hizbullah; Lo, Kong Mun *; Tiekink, Edward R. T. * (De Gruyter Open, 2020)
C12H15NO4, triclinic, P1̄ (no. 2), a = 7.4325(3) Å, b = 7.5171(3) Å, c = 23.7377(9) Å, α = 87.780(3)°, β = 89.105(3)°, γ = 61.299(4)°, V = 1162.42(9) Å3, Z = 4, Rgt(F) = 0.0566, wRref(F2) = 0.1652, T = 100(2) K.